Peace now! : American society and the ending of the Vietnam War - Jeffreys-Jones, Rhodri (Yale University Press, 1999)
Looking at American society and the ending of the Vietnam War, this book focuses on four social groups-students, African Americans, women and labor-and investigates their impacts on American foreign policy. 11 illustrations. How did the protests & support of ordinary American citizens affect their country's participation in the Vietnam War? This engrossing book focuses on four social groups that achieved political prominence in the 1960s & early 1970s-students, African Americans, women, & labor- & investigated the impact of each on American foreign policy during the war.